Conformity and controversies in the diagnosis, staging and follow‐up evaluation of canine nodal lymphoma: a systematic review of the last 15 years of published literature†. (14th July 2016) - Marconato, L.; Polton, G. A.; Sabattini, S.; Dacasto, M.; Garden, O. A.; Grant, I.; Hendrickx, T.; Henriques, J.; Lubas, G.; Morello, E.; Stefanello, D.; Comazzi, S.; et al.
Abstract: Diagnostic methods used in the initial and post‐treatment evaluation of canine lymphoma are heterogeneous and can vary within countries and institutions. Accurate reporting of clinical stage and response assessment is crucial in determining the treatment efficacy and predicting prognosis. This study comprises a systematic review of all available canine multicentric lymphoma studies published over 15 years. Data concerning diagnosis, clinical stage evaluation and response assessment procedures were extracted and compared. Sixty‐three studies met the eligibility criteria. Fifty‐five (87.3%) studies were non‐randomized prospective or retrospective studies. The survey results also expose variations in diagnostic criteria and treatment response assessment in canine multicentric lymphoma. Variations in staging procedures performed and recorded led to an unquantifiable heterogeneity among patients in and between studies, making it difficult to compare treatment efficacies. Awareness of this inconsistency of procedure and reporting may help in the design of future clinical trials.